A new technique to calculate the electronic structure of two-dimensional disordered systems - Yildiz, AK; Beeby, JL (Iop Publishing Ltd, 1997)
The purpose of this work is to investigate the electronic structure of two-dimensional structurally disordered solids by means of a method based on multiple-scattering theory. The theoretical technique is applied to some two-dimensional models which can be varied from the limit of a perfect to a completely disordered structure. The models are continuous structural networks with different-fold coordinations of atoms in planar structures. The spectral density is determined through a self-consistent approach. Using the spectral density, the convergence of the technique is analysed through calculations of the density of electronic states, and the variation of the density of electronic states with respect to varying disorder in the structure is determined. In particular, the convergence of the technique for the calculation of the density of electronic states as a function of the size of the matrix representation used is confirmed and it is shown that the degree of disorder in two-dimensional systems significantly influences the density of electronic states.
Keywords: States; Density